Pengaruh Tunjangan Sertifikasi Guru Terhadap Kinerja Guru pada SMAN 1 Lembang Jaya Kabupaten Solok - Emita, Syahril (Jurnal Menara Ekonomi : Penelitian dan Kajian Ilmiah Bidang Ekonomi, 2015)
This study entitled Effect of certification allowance against the performance of teachers inLembang Jaya SMA.N 1 Solok. Writers interested in researching this title is a phenomenonthat many writers see the benefits of certification are less smooth and dense paymentcertification of teachers teaching hours, so that the learning process is not optimalanymore. It is quite disturbing performance as a teacher educator who has beenpreoccupied by management certification courseThe population in this study was about 18 people and a sample of 18 people using totalsampling .Teknik Analasa data used to analyze this research that using simple regressionanalysis. Where the variables in this study are the benefits of certification as anindependent variable (X) and teacher performance as the dependent variable (Y).The results showed that the benefits of certification of teachers significantly influence theperformance of teachers in Lembang Jaya SMA.N 1 Solok. It can be seen from the systemsand patterns of teachers who are already teaching in accordance with the SOP andestablished by the SBC and Kemendikbud and motivated teachers in teaching.Keywords: Benefits of certification and performance